Tertiary Educators' Awareness of and Readiness to use Virtual Reality (VR) in Remote Online Learning - Wan Jumani, Fauzi; Noor Raha, Mohd Radzuan; Aisyah Khaleeda, Rosli; Ezihaslinda, Ngah; Awanis, Romli; Roslinda, Abd Wab; Wan Aslynn Salwani, Wan Ahmad (2023)
COVID-19 pandemic has transformed the conventional education landscape to online remote learning. However, this transition has brought about certain challenges such as low levels of student engagement and motivation, which raises the question of whether students are actually learning. Using Virtual Reality (VR) in teaching and learning (T&L) could increase engagement as it provides interactive experience that necessitates students’ online presence. Literature shows students are aware of VR benefits, yet not many tertiary educators are using VR. Thus, this study aims to investigate Malaysian tertiary educators’ awareness of VR and readiness to explore its potential in remote online T&L through a questionnaire survey adapted from previous studies that applied the Technology Acceptance Model (TAM) as their theoretical framework. Of 26 respondents, only 4 had VR experience in the classroom. While others lacked VR experience, their perceptions were positive, and they were aware of the challenges of using VR. It can be concluded these challenges are partly the reasons why VR is under-utilised. The findings implicate the need to train and familiarise tertiary educators in the use of VR for the continuous intention to use VR. It is believed that when more educators have more intimate knowledge of VR, the more students will benefit regardless if the classes are remote online or otherwise.